Last comics on Earth. 4, Across the Doodleverse - Brallier, Max; Pruett, Joshua (Brallier, Max. Last comics on Earth (Series) ;, 2026)
"The fourth and final installment of the New York Times bestselling graphic novel series based on the worldwide phenomenon The Last Kids on Earth! In this final LAST COMICS adventure, our superheroes must face a mysterious new threat: Someone is stealing kids' schoolwork-margin doodles and turning them into an army of ANIMATED sketches! WHAT CAN OUR heroes do against the manic, illogical brilliance of LIVING doodles?! While they fight, Boy Lightning's drawing arm is kidnapped by a new villain and taken into the wastelands beyond the borders of Apocalyptia. Now our team must brave AS YET unseen worlds in order to save Jack from the machinations of DOODLEHEAD! Can our heroes save the world from a doodle-pocalypse?" --